Tertiary Lymphoid Tissues Are Microenvironments with Intensive Interactions between Immune Cells and Proinflammatory Parenchymal Cells in Aged Kidneys - Yoshikawa, Takahisa; Oguchi, Akiko; Toriu, Naoya; Sato, Yuki; Kobayashi, Takashi; Ogawa, Osamu; Haga, Hironori; Sakurai, Satoko; Yamamoto, Takuya; Murakawa, Yasuhiro; Yanagita, Motoko (Journal of the American Society of Nephrology, 2023)
Visual Abstract Significance StatementEctopic lymphoid structures called tertiary lymphoid tissues (TLTs) develop in several kidney diseases and are associated with poor renal prognosis. However, the mechanisms underlying TLT expansion and their effect on renal regeneration remain unclear. The authors report that single-nucleus RNA sequencing and validation experiments demonstrate that TLTs potentially amplify inflammation in aged injured kidneys. Lymphocytes within TLTs promote proinflammatory phenotypes of the surrounding proximal tubules and fibroblasts within the TLTs via proinflammatory cytokine production. These proinflammatory parenchymal cells then interact with immune cells by chemokine or cytokine production. Such cell-cell interactions potentially increase inflammation, expand TLTs, and exacerbate kidney injury. These findings help illuminate renal TLT pathology and suggest potential therapeutic targets.BackgroundEctopic lymphoid structures called tertiary lymphoid tissues (TLTs) develop in several kidney diseases and are associated with poor renal prognosis. However, the mechanisms that expand TLTs and underlie exacerbation of kidney injury remain unclear.MethodsWe performed single-nucleus RNA sequencing (snRNA-seq) on aged mouse kidneys with TLTs after ischemia-reperfusion injury. The results were validated using immunostaining, in situ hybridization of murine and human kidneys, and in vitro experiments.ResultsUsing snRNA-seq, we identified proinflammatory and profibrotic Vcam1+ injured proximal tubules (PTs) with NFκB and IFN-inducible transcription factor activation. VCAM1+ PTs were preferentially localized around TLTs and drove inflammation and fibrosis via the production of multiple chemokines or cytokines. Lymphocytes within TLTs expressed Tnf and Ifng at high levels, which synergistically upregulated VCAM1 and chemokine expression in cultured PT cells. In addition, snRNA-seq also identified proinflammatory and profibrotic fibroblasts, which resided within and outside TLTs, respectively. Proinflammatory fibroblasts exhibited STAT1 activation and various chemokine or cytokine production, including CXCL9/CXCL10 and B cell-activating factor, contributing to lymphocyte recruitment and survival. IFNγ upregulated the expression of these molecules in cultured fibroblasts in a STAT1-dependent manner, indicating potential bidirectional interactions between IFNγ-producing CXCR3+ T cells and proinflammatory fibroblasts within TLTs. The cellular and molecular components described in this study were confirmed in human kidneys with TLTs.ConclusionsThese findings suggest that TLTs potentially amplify inflammation by providing a microenvironment that allows intense interactions between renal parenchymal and immune cells. These interactions may serve as novel therapeutic targets in kidney diseases involving TLT formation.